The Influence of the Living Values Education (LVE) Approach on Increasing Religious Moderation of PAI (Islamic Education) Teachers in Pekanbaru Indonesia - Rosidi, Imron; Soim, Muhammad; Arbi, Arbi; Kasmuri, Kasmuri (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2024)
Indonesian society has long been known to have an open and moderate religious character as the process of Islamization taking place in peaceful Indonesia. However, recently there has been a trend towards a "conservative turn", a hard, rigid and conservative religious attitude. This phenomenon has then targeted Islamic teachers. PAI teachers, as the "front guard" in the process of instilling Islamic knowledge and values, are very important figures in disseminating friendly, tolerant and open religious attitudes towards students. Through the Living Values Education (LVE) approach, teachers are given training on the values of religious moderation for PAI teachers at Pekanbaru City Public High Schools. This research uses a Participatory Action Research (PAR) approach. 20 PAI teachers were selected randomly, then they were given understanding through a living values education (LVE) approach. The results of this research show that there has been an increase in PAI teachers' understanding of moderate religion after being given living values education. These findings are useful for policy makers to apply this study model to spread religious moderation among Muslim communities.